Interference Impacts Working Memory in Mild Cognitive Impairment - Aurtenetxe, Sara; García-Pacios, Javier; del Río, David; López, María E.; Pineda-Pardo, José A.; Marcos, Alberto; Delgado Losada, Maria L.; López-Frutos, José M.; Maestú, Fernando (Frontiers in Neuroscience, 2016)
Mild cognitive impairment (MCI) is considered a transitional stage between healthy aging and dementia, specifically Alzheimer’s disease (AD). The most common cognitive impairment of MCI includes episodic memory loss and difficulties in working memory (WM). Interference can deplete WM, and an optimal WM performance requires an effective control of attentional resources between the memoranda and the incoming stimuli. Difficulties in handling interference lead to forgetting. However, the interplay between interference and WM in MCI is not well understood and needs further investigation. The current study investigated the effect of interference during a WM task in 20 MCIs and 20 healthy elder volunteers. Participants performed a delayed match-to-sample paradigm which consisted in two interference conditions, distraction and interruption, and one control condition without any interference. Results evidenced a disproportionate impact of interference on the WM performance of MCIs, mainly in the presence of interruption. These findings demonstrate that interference, and more precisely interruption, is an important proxy for memory-related deficits in MCI. Thus the current findings reveal novel evidence regarding the causes of WM forgetting in MCI patients, associated with difficulties in the mechanisms of attentional control.